Evaluación agronómica y de producción de los maices hibridos ´30f35´, ´30k75´ y ´triunfo nb-7253´ con diferentes niveles de fertilización química y densidades poblacionales, en la zona de baba provincia de Los Ríos - Santintevan Cabero, Irvin Jasmany (2012)
In the land belonging to Mr. Mariano Avila, located at Km 9.5 road Babahoyo - Baba, province de Los Ríos; was established in this experiment to test the genetic potential of hybrid corn '30F35, '30K75 'and'' NB Triumph - 7253 ', and in order to identify the most appropriate population density and the most suitable chemical fertilization program to maximize grain yield, assessing the effects of the interaction between chemical fertilizer levels and population density, and perform economic analysis of grain yield based on the cost of subtreatments. Population densities were: 62500; 71428 83333 plants per hectare; and levels of chemical fertilization were: 60 - 60-70; 120 80-140; 180 - 100 - 210 and 92 - 23-30 Kg/has nitrogen, phosphorus and potassium, respectively. The experimental design "Divided plots" was used in three repetitions; where the main plots correspond to hybrids (treatments); combinations and levels of chemical fertilization - population densities (subtratamientos) as experimental subparcelas. The experimental subplot was constituted by 4 rows of 5 m in 76 length, separated at 0.80 m (62500 pl/has), 0.70 m (714289 l/ has) and 0,60 m (83333 pl/has), giving 18 areas; 11,2 and 9,60 m2, respectively. The useful area was contituída by the 2 Central rows of each experimental subplot; remaining areas of 9.0; 5.6 and 4.8m2 for 62500 densities; 71428 83333 plants per hectare, on its agenda...........